2006
DOI: 10.4049/jimmunol.176.3.1889
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Effects of Tweak/Fn14 Interactions in Glomerular Mesangial Cells

Abstract: TNF-like weak inducer of apoptosis, or TWEAK, is a relatively new member of the TNF-ligand superfamily. Ligation of the TWEAK receptor Fn14 by TWEAK has proinflammatory effects on fibroblasts, synoviocytes, and endothelial cells. Several of the TWEAK-inducible cytokines are important in the pathogenesis of kidney diseases; however, whether TWEAK can induce a proinflammatory effect on kidney cells is not known. We found that murine mesangial cells express cell surface TWEAK receptor. TWEAK stimulation of mesang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
187
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(193 citation statements)
references
References 48 publications
5
187
0
Order By: Relevance
“…In contrast, the only TNF family members that have been implicated in CXCL10 expression are TNF-a (44), CD40L (45,46). and TWEAK (47), all in nonlymphoid cell types. The finding that a T cell costimulatory receptor induces chemokine expression during priming is novel and begs for a conceptual interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the only TNF family members that have been implicated in CXCL10 expression are TNF-a (44), CD40L (45,46). and TWEAK (47), all in nonlymphoid cell types. The finding that a T cell costimulatory receptor induces chemokine expression during priming is novel and begs for a conceptual interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TWEAK regulation of vastly different cellular responses is probably due, at least in part, to cell type-specific differences in Fn14-mediated intracellular signalling events. 72 reported that intravenous TWEAK injection (200 µg) induces MCP1 and IP10 mRNA expression in kidney. This geneexpression data, in combination with additional findings demonstrating that anti-TWEAK neutralizing monoclonal antibodies reduce inflammatory cell infiltration in mouse models of rheumatoid arthritis47 , 83 and multiple sclerosis 85 (see below) and that Fn14-null mice display a deficient inflammatory response following tissue injury 31 , is consistent with the proposal that TWEAK is in fact a pro-inflammatory cytokine.…”
Section: Tweak-dependent Fn14 Signallingmentioning
confidence: 99%
“…Besides inducing proinflammatory cytokines and chemokines, TWEAK can also affect cell proliferation and survival (13,14,26). As both kidney cell proliferation and apoptosis have been described in LN (27)(28)(29), we assessed renal cell proliferation and apoptosis by Ki-67 and caspase 3 staining, respectively.…”
Section: Fn14-deficient Mice Have Reduced Renal Igg Deposition Cytokmentioning
confidence: 99%
“…Recently, we have shown that Fn14 is expressed by murine kidney mesangial cells and podocytes, and that TWEAK stimulates mesangial cells to secrete high levels of potent proinflammatory chemokines including MCP-1, RANTES, IP-10, and KC (13). Justo et al (14) reported that renal tubular cells display Fn14 as well.…”
mentioning
confidence: 99%